Re-ordering the Landscape: Landed Elites and the New Urban Aristocracy in Manchester - O’Reilly, Carole (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2011)
This paper examines the relationship between the landed aristocracy in the vicinity of Manchester and the “urban aristocracy” of the municipal authority and their role in the development of municipal parks in the city in the late nineteenth and early twentieth centuries. It contests the view that landed elites had little impact on the development of the environs of Manchester during this period and argues that their social and economic influence was gradually replaced by that of the municipal authority in a reordering of the social landscape. It also re-examines the role of debt in the decline of the traditional landed elites and argues that, in the case of the two families studied here, debt became a problem much earlier than others have suggested and was often chronic and persistent.The aristocracy of the Manchester area and the sales of their estates have been marginalized in existing histories, as this group has been perceived as peripheral to the city’s development. It is the contention of this paper that they played a more active role in their localities than previously believed and that they forged significant networks with local authorities, families, businesses, and institutions. Their economic relationships with the new business elite in Manchester, represented primarily but not solely by the municipal authority, provide an opportunity to examine the reordering of the social landscape as the landed elite sought to remove themselves from the city.Having symbolized the social and economic power of the aristocracy, the land now represented the civic pride and enterprise of the municipal authority. This paper reveals the complex interplay of power between these elite groups and sheds a unique light on urban land usage and the formation of leisure spaces in the city.